2021
DOI: 10.3390/genes12121879
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing Identifies the HLA-DQA1*03:03 Allele in the Type 1 Diabetes Risk-Associated HLA-DQ8 Serotype

Abstract: The highest genetic type 1 diabetes risk is conferred by HLA class II haplotypes defined by alleles at the HLA-DR and -DQ loci. The combination of HLA-DQA1*03:01 and DQB1*03:02 alleles (summarized as ‘HLA-DQ8′) is reported to be among the two most prevalent HLA class II haplotypes in Caucasian type 1 diabetes patients. This classification is based on conventional genotyping of exon 2 of the DQ gene locus and excludes exon 3. In this study, HLA genotyping on the type 1 diabetes susceptibility loci HLA-DRB1, DQA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…HLA-DR4 may also be associated with DQ7 but this typing combination is not associated with T1D, underlining the importance of the inclusion of HLA-DQ with HLA typing. 22 In ∼90% of white children diagnosed with T1D, either the HLA-DR4/DQ8 or the HLA-DR3/DQ2 haplotype is found, 23 consistent with our data which showed a prevalence of 89.5% for either haplotype in our transplant recipients. HLA class II antigens including HLA-DQ2∗-A05 and HLA-DQ8 are expressed by human beta cells in T1D and may be a direct target of autoreactive CD4+ T cells, 24 explaining this association.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…HLA-DR4 may also be associated with DQ7 but this typing combination is not associated with T1D, underlining the importance of the inclusion of HLA-DQ with HLA typing. 22 In ∼90% of white children diagnosed with T1D, either the HLA-DR4/DQ8 or the HLA-DR3/DQ2 haplotype is found, 23 consistent with our data which showed a prevalence of 89.5% for either haplotype in our transplant recipients. HLA class II antigens including HLA-DQ2∗-A05 and HLA-DQ8 are expressed by human beta cells in T1D and may be a direct target of autoreactive CD4+ T cells, 24 explaining this association.…”
Section: Discussionsupporting
confidence: 91%
“… 27 Individuals in this study most likely have DR4 in association with DQ8 typing. 23 Alternative mechanisms that may protect the transplanted beta cells include CD8+ T cell exhaustion 28 secondary to immunomodulation. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that the strongest associated haplotype was DRB1*03:01:01~DQA1*05:01:01~DQB1*02:01:01 [OR (95% CI) = 4.1 (2.61–6.63), P c = 8.7 x 10 -10 ], which confers high risk of T1D, and is well-documented in Arab, Korean, and Caucasian populations ( 7 , 9 , 40 ). Furthermore, DRB1*04:05:01~DQA1*03:03:01~DQB1*03:02:01 [OR (95% CI) = 5.4 (1.64–23.16), P c = 0.01] is the second-most significant haplotype conferring high risk of T1D and has only been reported once in a European population study ( 47 ). Enczmann et al., suggested that the identification of this haplotype is possible using high-resolution NGS, which was employed in our study, that genotyped both exon 2 and 3 of the DQ gene for allele classification.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, genetic studies in the past found over 50 associated regions; however, most associated variants (except HLA, PTPN22, IFIH1, CTSH, TYK2, and FUT2) are involved in gene regulation and only HLA-II, INS, and PTPN22 show substantial effects on T1D. Taken together, they explain fewer than 50% of the heritability in T1D, and integrative multi-omic approaches, such as genome and transcriptome analysis, epigenetics, and chromatin conformation, in relevant cell types and disease context will be important to uncover the rest of the causative variants [49,75,79]. Furthermore, T1D-linked SNPs alter the expression of many genes involved in immune signalling and β-cell destruction, as well as in viral responses.…”
Section: Regulating the Effects Of Cytokines Inside β-Cells For Proap...mentioning
confidence: 99%